2017
DOI: 10.3892/mmr.2017.7332
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-543 inhibits proliferation, invasion and induces apoptosis of glioblastoma cells by directly targeting ADAM9

Abstract: Glioma is the most common type of malignant brain tumor in humans and accounts for 81% of all malignant brain tumor cases in adults. The abnormal expression of microRNAs (miRs) has been reported to be important in the formation and progression of various types of human cancer, including glioblastoma (GBM). Therefore, studies into the expression, and roles of microRNAs as diagnostic and prognostic markers, as well as their therapeutic value for patients with GBM are warranted. The expression and roles of miR‑54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…Here, we focused on the part that miR-543 takes in breast cancer progression, attempting to provide additional new information regarding biotarget therapy for breast cancer. Previously, lower miR-543 expression was reported in endometrial cancer [ 30 ] and glioma [ 31 ], which is in accordance with the present observation that miR-543 displayed a reduced level in breast cancer progression. In the present study, functionally, miR-543 acted as an anti-tumor miRNA in breast cancer and participated in regulating cell viability, proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we focused on the part that miR-543 takes in breast cancer progression, attempting to provide additional new information regarding biotarget therapy for breast cancer. Previously, lower miR-543 expression was reported in endometrial cancer [ 30 ] and glioma [ 31 ], which is in accordance with the present observation that miR-543 displayed a reduced level in breast cancer progression. In the present study, functionally, miR-543 acted as an anti-tumor miRNA in breast cancer and participated in regulating cell viability, proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the involvement of ADAMs in cancer, ADAMs can be regulated by miRNAs to modulate the progression of tumorigenesis (37)(38)(39)(40)(41)(42)(43)(44)(45). A previous study revealed that miR-552 targets ADAM28 in colorectal cancer and enhances the metastasis of cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…It can promote apoptosis by decreasing ZBTB20 in glioblastoma cell ( Liu et al, 2018a ). There is a downregulation of miR-543 in glioblastoma and its upregulation can induce apoptosis by targeting ADAM9 ( Ji et al, 2017 ). MiR-152-3p affected the apoptosis of glioblastoma cells via NF2 overexpression ( Sun et al, 2017 ).…”
Section: Non-coding Rnas and Brain Tumorsmentioning
confidence: 99%